Vibration Response Analysis of Last Stage LP Turbine Blades for Variable Size of Crack in Root. (2016) - Shukla, Akash; Harsha, S.P.
Abstract: This paper is intended to find the variation in vibration response of blades with the crack size of fir tree root free standing blades. Generation of crack in blade root causes the loss of stiffness in the vicinity of blade root. It results in shifting of natural frequencies and redistribution of dynamic and static stress in the blade root which may cause failure of the blade. A 3D finite element model of a blade and its fir-tree roots has been analyzed. Results of FEM study are validated by experimental results of cracked blades. Finally the variation in natural frequency and mode shapes for different sizes cracked blades are studied.